(3GdaWQjGJ GdWHjI (B/s - (3TQja, ajGV eMeOs 1946- ((3HZOGO (B:s (3GdPGcQI ddfTQ hGdJhRjY,s, 2012)
(3jJfGhd cJGH (B((3GdaWQjGJ GdWHjI(B) (3hGdPj bGe HJCdjag GdOcJhQ ajGV eMeO TQja aj MhGdj (B(608) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdWajdjGJ GdWHjI(B)(3, eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3MjGJjI GdaWQjGJ GdWHjI, GdaUd GdKGfj (B: (3GdaWQjGJ ceeQVGJ HTQjI, GdaUd GdKGdK (B: (3CeQGV GdMSGSjI GdaWQjI, GdaUd GdQGHY (B: (3GdSehe GdaWQjI hGdJSee GdaWQj, GdaUd GdNGeS (B: (3GdJSee HGdaWQjGJ, GdaUd GdSGOS (B: (3GdCeQGV GdaWQjI GdSWMjI (B... (3hZjQgG ef GdehVhYGJ(B.s
(3bGFeI eUWdMGJ (B: (3UaMI (B583.s
(3HHdjhLQGajI (B: (3UaMI (B529-608.s
Keywords: (3GdaWQjGJ GdWHjIs